Potential for the geographic diversification of deciduous fruit growing in Uruguay - Linari, Gabriela; Gazzano, Inés; Achkar, Marcel (Agrociencia Uruguay, 2022)
The deciduous fruit growing in Uruguay is geographically concentrated in the south and expresses a high climatic vulnerability that can compromise food sovereignty and the continuity of production units. The objective of the work was to identify geographic areas of the Uruguayan territory with potential for the development of deciduous fruit growing based on the main biophysical variables that condition production. The availability of cold and the suitability of the soils were considered, and complemented with the distance to the main distributor market and the distance to towns with more than 5,000 inhabitants. The variables were weighted and integrated into a GIS based on the greatest combination between them. It was identified that 35.6% of the territory presents a high and very high potential for the production of deciduous fruit trees, which provides elements to discuss agroecological transition proposals based on the geographical diversification of production.